An Experimental Study: Creative Problem-Solving Learning Model with Kebumen Tourism Realistic Approach to Improve Numerical Literacy toward 8th-Grade Students - Liadiani, Anifa Mirza; Mariani, Scolastika (Department of Mathematics, Universitas Negeri Semarang, 2023)
The preliminary study found that students who reached the minimum competency limit of numerical literacy in Asesmen Kompetensi Minimum (AKM) 2021 were less than 50% and below the average value. Thus, this research aimed to determine whether the Creative Problem-Solving (CPS) learning model with Kebumen tourism realistic approach can improve numerical literacy. This research used a quantitative approach which was a quasi-experimental posttest-only design. The population studied was 243 8th-grade students of SMP Negeri 2 Kutowinangun in Kebumen for the academic year 2022/2023 with 2 classes as the sample which was obtained by random sampling. The instruments used were numerical literacy questions paper and the blueprint, answer key, and scoring guidelines. The conclusion was the CPS learning model with Kebumen tourism realistic approach was effective for increasing the numerical literacy of the population rather than the learning model applied by the class teacher. It was proved by these conditions: (1) students’ numerical literacy test mean value in the experimental group achieved individual learning mastery, (2) the proportion of students' numerical literacy test value in the experimental group achieved classical learning mastery, (3) the numerical literacy test mean value of the experimental group is better than the numerical literacy test mean value of the control group.